Collaborative and participatory approaches to cocoa variety improvement: Final report of the CFC/ICCO/Bioversity project on “Cocoa Productivity and quality improvement: a Participatory Approach” (2004-2010) - Eskes, A.B.; CFC; International Cocoa Organization; Bioversity International (2011)
This Final Report summarizes the outcomes of the Closing Workshop of the CFC/ICCO/Bioversity project on “Cocoa Productivity and Quality Improvement: a Participatory Approach”, convened at the end of May 2010 in Accra, Ghana. The workshop formally marked the conclusion of the project that was launched in June 2004, but which was building on the achievements of the CFC/ICCO/IPGRI project on “Cocoa Germplasm Utilization and Conservation: a Global Approach” implemented between 1998 and 2004. Thus many of the results presented here reflect the work done over a long period of time